Sterile inflammation in liver transplantation - Kahan, Riley; Cray, Paul L.; Abraham, Nader; Gao, Qimeng; Hartwig, Matthew G.; Pollara, Justin J.; Barbas, Andrew S. (Frontiers in Medicine, 2023)
Sterile inflammation is the immune response to damage-associated molecular patterns (DAMPs) released during cell death in the absence of foreign pathogens. In the setting of solid organ transplantation, ischemia-reperfusion injury results in mitochondria-mediated production of reactive oxygen and nitrogen species that are a major cause of uncontrolled cell death and release of various DAMPs from the graft tissue. When properly regulated, the immune response initiated by DAMP-sensing serves as means of damage control and is necessary for initiation of recovery pathways and re-establishment of homeostasis. In contrast, a dysregulated or overt sterile inflammatory response can inadvertently lead to further injury through recruitment of immune cells, innate immune cell activation, and sensitization of the adaptive immune system. In liver transplantation, sterile inflammation may manifest as early graft dysfunction, acute graft failure, or increased risk of immunosuppression-resistant rejection. Understanding the mechanisms of the development of sterile inflammation in the setting of liver transplantation is crucial for finding reliable biomarkers that predict graft function, and for development of therapeutic approaches to improve long-term transplant outcomes. Here, we discuss the recent advances that have been made to elucidate the early signs of sterile inflammation and extent of damage from it. We also discuss new therapeutics that may be effective in quelling the detrimental effects of sterile inflammation.